A case report: Severe disseminated infection caused by Strongyloides stercoralis in an immunocompromised patient by metagenomic next-generation sequencing - Xu, Qinfu; Xi, Xiaotong; Feng, Dan; Sang, Qian; Sheng, Yanbing; Ding, Ran; Xu, Aiguo (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Strongyloides stercoralis (S. stercoralis) is a widely distributed nematode in the tropical and subtropical regions, which may cause severe disseminated infection in immunocompromised individuals. Due to nonspecific clinical presentation and inadequate performance of conventional diagnostic methods, the disease caused by S. stercoralis is difficult to be diagnosed. Case description: We reported a 75-year-old male patient with severe disseminated infection caused by S. stercoralis. The patient had a history of seasonal bronchitis for many years and took prednisone for a long time. At first, no pathogens were detected by clinical tests, but S. stercoralis was identified in bronchoalveolar lavage fluid (BALF) and blood using metagenomic next-generation sequencing (mNGS). Subsequently, nematode larva were detected in stool and sputum for many times through routine tests. Combined with mNGS results and clinical symptoms, the patient was finally diagnosed with severe disseminated infection caused by S. stercoralis. Conclusion: The clinical manifestations of S. stercoralis disease are not specific, thus early and accurate diagnosis is very important. mNGS has certain advantages in S. stercoralis detection and can effectively identify the pathogens even at a low gene coverage. This case report supports the value of mNGS in diagnosing of severe disseminated infection caused by S. stercoralis in an immunocompromised patient.